Switzerland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper on Switzerland models the evolving behavior of the Swiss franc relative to the world's major reserve currencies and considers possible reasons for the shifts. Economic fundamentals, including country-partners and currency of denomination of Swiss trade and finance, are likely to affect which currencies the franc co-moves with, although these factors tend to change only slowly. The behavior of the Swiss franc may have also been affected by the global financial crisis and its aftermath, as well as the shift in recent years from synchronized to divergent monetary policies by the major central banks. Identifying reserve currency blocks and the de facto behavior of currencies is an ongoing pursuit. The two dimensions of exchange regimes-the anchor currency (basket) and the degree of exchange rate flexibility-should be identified simultaneously. The implied regimes align well with Switzerland's de facto exchange rate arrangements and monetary policy frameworks. The approach used in this paper identifies how the franc co-moves with the major reserve currencies but is agnostic about the driving forces behind these moves.